The Relationship between Demographic Characteristics and Disaster Preparedness for Facing Landslides in Rural Areas of Indonesia - Nurhafidin Ramadhani; Rismawan Adi Yunanto; Baskoro Setioputro; Ruris Haristiani (Nursing and Health Sciences Journal (NHSJ), 2024)
Indonesia, positioned amidst two oceanic continents, experiences varying rainfall intensities due to its tropical rainy climate, significantly impacting soil stability and rendering it prone to landslides. This study investigates community preparedness for landslides, focusing on demographic characteristics' influence. We used cross sectional method with utilizing an observational analytic approach. The data was collected from 89 respondents using the LIPI-UNESCO/ISDR questionnaire. The sampling technique used is simple random sampling using a computer application. Data analysis uses Spearman rho analysis to determine the correlation of each variable. Findings reveal a significant correlation between age and education with disaster preparedness, whereas previous disaster experience showed no correlation. Most respondents displayed inadequate preparedness, indicating a pressing need for enhanced disaster management efforts. The study underscores the imperative for targeted interventions to bolster community resilience, emphasizing education and awareness initiatives to bridge preparedness gaps. Overall, the findings provide valuable insights for policymakers and disaster management authorities in formulating proactive strategies to mitigate landslide risks and enhance community resilience in rural areas.